Empowerment, Communication, and Navigating Care: The Experience of Persons With Spinal Cord Injury From Acute Hospitalization to Inpatient Rehabilitation - Krysa, Jacqueline A.; Gregorio, Marianne Pearl; Pohar Manhas, Kiran; MacIsaac, Rob; Papathanassoglou, Elizabeth; Ho, Chester H. (Frontiers in Rehabilitation Sciences, 2022)
Background: Spinal cord injury (SCI) results in long-term functional impairments that significantly impact participation and role in the community. Newly injured persons are often reintroduced to the community with significant deficits in knowledge, including how to access and navigate community resources and supports. This warrants a better understanding of the patient experience of in-hospital care and discharge planning to ensure individuals with SCI are best supported during transitions in care and while living in the community. Objective: To explore the lived experience of persons with acute SCI and their perceptions of care, focusing on the initial hospital experiences to inpatient rehabilitation. Methods: A phenomenological research study was conducted using semi-structured interviews. Eligible participants had differing etiologies of SCI (including non-traumatic and traumatic SCI), were over the age of 18 at the time of initial care, and experienced acute hospital and inpatient rehabilitation at an Alberta-based institution within the last 10 years. One-on-one interviews took place between March and June 2021 over telephone or virtual platforms (Zoom). Interview transcripts, and field notes developed the text, which underwent hermeneutic analysis to develop central themes. Results: The present study included 10 participants living with an SCI in Alberta, Canada. Most participants (80%) were male. Participants’ age ranged from 24 to 69 years. The median years since initial SCI was 3 years. Interviews lasted 45 to 75 minutes. Seven participants identified as having a traumatic SCI injury and three identified as having a non-traumatic SCI. The interplay between empowerment and disempowerment emerged as the core theme, permeating participants’ meanings and perceptions. Three main themes emerged from the interviews regarding the perceptions of the SCI patient experience. Each theme represents a perception central to their inpatient experience: desire to enhance functional independence to empower confidence and self-management; need for effective communication with healthcare providers to support recovery; and navigating appropriate care supports to enhance preparedness for discharge and returning home. Conclusion: This study demonstrates the significant need to enhance education of person/family-centred SCI care, foster positive communication between care recipients and care providers, and facilitate better in-hospital access to appropriate navigation and wayfinding supports.